ASYLUM SEEKER OR SEEKER OF A BETTER LIFE? WHAT MAKES A DIFFERENCE WITHIN CATEGORIZATION? - Lindblom-Häkkinen, Sari; Anttila, Maisa (Border Security and Management, 2018)
Migrants are often classified based on the reasons of emigration and way of travel. In this paper our aim is to focus on the stories and discourses of humanitarian migration from different perspectives offering first; the new category of classification of the migrants, second; the new way to face asylum seekers and third; to make a questionable necessity of classification over all: what kind of added value the classification gives and to whom in the end of the day? We are focusing on this phenomenon in the context of border security. We will identify how the consequences of natural forces (e.g. earthquake) impacts emigration. In this paper, we argue that the individual life situations, cultural discourses and societal factors all are important for understanding the phenomenon of migration. Thus, suggest of a new category of migration, is “seeking better life”. However, at the same time we recognize that often the categories overlap and depend on the perspective.